2022
DOI: 10.1002/biot.202100470
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the potential of Schizochytrium sp. HX‐308 for microbial lipids production from corn stover hydrolysate

Abstract: Schizochytrium sp. has received increasing attention as promising commercial resource for the sustainable production of lipids, due to their fast growth rate and high lipid content. However, the price of glucose represents a significant proportion of the total substrate cost. Therefore, in this study, the lignocellulosic hydrolysate of corn stover hydrolysate (CSH) was used as low‐cost culture medium to replace glucose in Schizochytrium sp. fermentation. When Schizochytrium sp. HX‐308 was fermented with 20% gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
(46 reference statements)
0
7
0
Order By: Relevance
“…The suspension was stirred by a propeller agitator (4) powered by an induction motor (5). The retentate outlet (6) was closed, and the permeate was collected in the tank (7). Permeate flow was measured using a cylinder and stopwatch.…”
Section: Study On Reactor Hydrodynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The suspension was stirred by a propeller agitator (4) powered by an induction motor (5). The retentate outlet (6) was closed, and the permeate was collected in the tank (7). Permeate flow was measured using a cylinder and stopwatch.…”
Section: Study On Reactor Hydrodynamicsmentioning
confidence: 99%
“…Membranes were concentrically placed around the propeller stirrer (2) (diameter, d = 11 cm). A guiding tube (d = 13 cm) is located between the membranes and the propeller(7). The suspension of the feedstock (i.e., grounded lignocellulosic waste) and enzymes in the buffer flow into the reactor by the inlet (4).…”
mentioning
confidence: 99%
“…Schizochytrium sp., a heterotrophic marine organism, has been used industrially to produce docosahexaenoic acid (DHA). [1][2][3] The typical condition of laboratory scale cultivation for Schizochytrium sp. is artificial seawater, which requires a large amount of water resources and costs a lot.…”
Section: Introductionmentioning
confidence: 99%
“…Schizochytrium sp., a heterotrophic marine organism, has been used industrially to produce docosahexaenoic acid (DHA) 1–3 . The typical condition of laboratory scale cultivation for Schizochytrium sp.…”
Section: Introductionmentioning
confidence: 99%
“…Its DCW and total lipid can reach 165.0 and 113.6 g/L, respectively, under specific circumstances [ 29 ]. Our previous research had shown that HX-308 has relatively high tolerance to furfural derivatives and organic acids found in lignocellulosic hydrolysates [ 30 ]. However, HX-308 is unable to use xylose to safeguard cell growth, which limits the utilization of lignocellulose.…”
Section: Introductionmentioning
confidence: 99%